CHRONIC KIDNEY DISEASE: PATHOGENESIS, CLINICAL FEATURES AND MODERN MANAGEMENT (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
Chronic Kidney Disease (CKD) is a progressive and irreversible decline in renal function lasting longer than three months. It represents a major global health burden due to its association with cardiovascular morbidity, end-stage renal disease (ESRD), and increased mortality. This study analyzes the pathogenesis, risk factors, diagnostic criteria, clinical manifestations, complications, and current treatment approaches of CKD.